Prevalence and bleeding pattern of endometrial polyp in women presenting with abnormal uterine bleeding at Maharaj Nakorn Chiang Mai Hospital - Sasiya Metatratip; Tawiwan Panthasri; Opas Sreshthaputra; Surapan Khunamornpong; Sumalee Siriaunkgul (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To study the prevalence and bleeding pattern of endometrial polyp in women with abnormal uterine bleeding.Materials and Methods: This was a retrospective descriptive study on 515 female patients with abnormal uterine bleeding at Maharaj Nakorn Chiang Mai Hospital from January 1, 2006 to December 31, 2008. These women had been investigated wityh either fractional curettage, endometrial sampling or hysteroscopy. The diagnoses were confirmed by pathological reports.Results: The prevalence of endometrial polyp was 12.8%, at the mean age of 46.7 years old (range, 30-69 years old), which did not correlate with the age, reproductive status or methods of contraception (p=0.78, 0.75 and 0.45 respectively). However, in the postmenopausal group, the prevalence was significantly higher in the patients who received hormone replacement therapy (HRT) compared with those without it (31.2% vs 7.1% , p=0.004). The most common bleeding pattern of the patients with endometrial polyp was hypermenorrhea (58.2%).Conclusion: The prevalence of the endometrial polyp was 12.8%, which does not correlate with the menstrual status, contraception methods or age. The most common bleeding pattern of the patients with endometrial polyp was hypermenorrhea (58.2%).